Polycystic Ovary Syndrome - treatment update - Szymura, Marta; Molenda, Marek Jarosław; Woszczyńska, Oliwia Brygida; Rycąbel, Paweł Maciej; Romaniuk, Mateusz; Wachowska, Maria; Paniak, Mateusz; Wojciechowska, Agnieszka Ewelina; Krawczyk, Michał Brunon; Sowiński, Wojciech Jan (Quality in Sport, 2025)
Introduction: Polycystic Ovary Syndrome (PCOS) is one of the most common endocrine disorders. It gets its name from the characteristic appearance of the ovaries observed in ultrasound imaging. Statistically, PCOS affects about 4-12% of women of reproductive age. PCOS can have a variety of symptoms and courses, and its causes have not been fully understood. Women with PCOS are at a higher risk of developing diabetes, hypertension, hyperlipidemia, and endometrial cancer compared to their healthy peers. The purpose of our work is to discuss the available methods used in the treatment of this syndrome. Research Objective: The primary aim of this literature review is to show available methods of treating PCOS based on the latest scientific research. Materials and methods: The review was based on the analysis of materials collected in the "Pubmed" database, books and other scientific articles. Keyworlds: Endocrine disorder; Polycystic Ovary Syndrome; Hyperandrogenism; Treatment; Infertility; Ovulation Conclusions: Polycystic Ovary Syndrome (PCOS) remains an important issue that affects women’s functioning and their hormonal balance. A review of the literature has shown that the use of medications and supplements in the form of herbs and plants has a positive impact on women's hormonal health, contributing to the regulation of the menstrual cycle and the stimulation of ovulation. Further research on the use of herbs is necessary, as based on the current sources, no definitive conclusions can be drawn.